Use of traditional and complementary medicine for maternal health and wellbeing by African migrant women in Australia: a mixed method study - Zewdneh Shewamene; Tinashe Dune; Caroline A. Smith (BMC, 2020)
Abstract Background Traditional medicine serves as a form of primary health care for more than 80% of African populations. Currently, there is no research documenting if and how African migrant communities engage with their traditional health practices and beliefs after they resettle in Western countries. The aim of this study was to examine African migrant women's experiences and perspectives about traditional and complementary medicine use in relation to their maternal health and wellbeing in Australia. Methods We conducted a mixed method study between December 2016 and October 2017. Questionnaires were completed by 319 women and 15 in-depth interviews were conducted among African migrant women residing across the Sydney metropolitan area, Australia. Survey data were analysed using SPSS (version 23) and logistic regression model was used to test associations. Qualitative data were analysed thematically using NVivo 11 software to identify themes and conceptual categories in the participants' responses. The study was informed by Andersen's Socio-behavioural model of health service utilisation. Results The findings indicated that use of traditional and complementary medicine was high and continued to be well used following African women's resettlement in Australia. The survey found that 232 (72.7%) women use some form of traditional and complementary medicine for maternal health and wellbeing purposes. Most women (179, 77.2%) reported that maintaining their maternal health and wellbeing was the most common reason for use. The interview findings indicated that access to traditional medicine included making requests from relatives and friends who travelled to Africa looking for a similar medicinal plant in Australia and preparing home remedies with advice from family members and healers back in Africa. Age ≥ 35 years (OR, 16.5; 95%CI, 6.58-41.5; p < 0.001), lower education (OR, 24; 95%CI, 8.18-71.1; p < 0.001), parity (OR, 7.3; 95%CI, 1.22-42.81; p = 0.029), and lower income (OR, 2.7; 95%CI, 1.23-5.83; p = 0.013) were strong predictors of traditional medicine use. Conclusion Use of traditional and complementary medicine among African migrant women in Sydney remained high following resettlement in Australia. As noted in Andersen's sociobehavioural model of health service utilisation, specific predisposing and enabling factors including age, education and income were associated with use of traditional and complementary medicine.